(untitled) (Argos, 2025)
The purpose of this paper is to read critically 20th century translations of Martial. Taking as a starting point the traductological categories that Antoine Berman defines in La traduction et la lettre ou l’Auberge du lointain (1999), we will study the peculiarities of philological and literary translation. Our corpus includes translations in English, French, Spanish and Italian: if not exhaustive, it is however representative of the most significant tendencies in translation in the last hundred years.